A Small UWB Antenna with Dual Band-Notched Characteristics - J. Xu; D.-Y. Shen; G.-T. Wang; X.-H. Zhang; X.-P. Zhang; K. Wu (International Journal of Antennas and Propagation)
A small novel ultrawideband (UWB) antenna with dual band-notched functions is proposed. The dual band rejection is achieved by etching two C-shaped slots on the radiation patch with limited area. A single band-notched antenna is firstly presented, and then an optimized dual band-notched antenna is presented and analyzed. The measured VSWR shows that the proposed antenna could operate from 3.05 to 10.7 GHz with VSWR less than 2, except two stopbands at 3.38 to 3.82 GHz and 5.3 to 5.8 GHz for filtering the WiMAX and WLAN signals. Radiation patterns are simulated by HFSS and verified by CST, and quasiomnidirectional radiation patterns in the H-plane could be observed. Moreover, the proposed antenna has a very compact size and could be easily integrated into portable UWB devices.